Influence of obesity and androgen deficiency on prostatic blood circulation - I. A. Tyuzikov; А. G. Martov; Yu. S. Kalinchenko (Бюллетень сибирской медицины)
In Study at 120 Diabetes Mellitus II type men the high frequency Obesity (71,7%) and Androgen Deficiency (52,8—64,5% of the patients depending on a degree of the indemnification) and them pathogenic authentic communications were shown. The blood level of total testosterone was represented by the critical factor of Prostatic arterial Blood Circulation. Obesity and Androgen Deficiency are seem as independent risk factors to development of ischemic prostatopathy, such as Prostatic blood circulation Disorders can develop earlier than other variants of the diabetic microangiophaty.